A proteção social do trabalhador da economia informal: um estudo sobre os Microempreendedores Individuais (MEI) no Brasil - Bertosso, Henrique (2024)
The informal economy has been expanding its proportion in the context of the Brazilian labor market. One of the segments of workers in the informal economy that has been standing out in this direction is that of Individual Microentrepreneurs (MEI), a legal entity implemented in 2008. The thesis aims to investigate Individual Microentrepreneurs (MEIs), identifying the social protection policies implemented in the areas of health and social security, their scope and effective results. It is based on an applied study, with a qualitative approach, through semi-structured interviews with 16 individual microentrepreneurs in the southern region of Brazil, accessed through a convenience sample. During the development of the study, three academic productions were carried out: Academic Production I investigated differences in social security contributions and hours worked between formal and informal workers; Academic Production II examined the communication of the Federal Government and Sebrae to MEIs, focusing on health and social security; Academic Production III explored the expectations and realities of MEI formalization, analyzing legislative and structural changes that affect these workers and suggesting ways to strengthen their social protection. The results identify the MEI as a significant strategy to promote the formalization of workers and entrepreneurs in Brazil, evidenced by the growing number of registrations and by representing the sole source of income for 76.0% of them. Being an “entrepreneur of oneself” influences the perceptions and practices of MEIs, giving meaning to autonomy, but also increasing levels of stress and emotional overload. Despite their formal status, MEIs operate in an environment in which the boundaries between formal and informal are fluid, sharing characteristics with the informal economy. Economic insecurity can lead to neglect of the health needs of these workers. Income instability makes it difficult to regularly make payments to the INSS, with significant variations in retirement preparation. Thus, like other workers in the informal economy, MEIs face additional challenges in preparing for retirement, especially in contexts of limited social safety nets.